Investigation of ammonium–lauric salt as shale swelling inhibitor and a mechanism study - Jie Zhang; Weimin Hu; Li Zhang; Tiehu Li; Dan Cai; Gang Chen (Adsorption Science & Technology)
In this work, a series of ammonium–lauric salts (ALS) was prepared with lauric acid and amines as small molecular shale swelling inhibitor. The inhibitors were screened by the linear expansion test first, and the result shows that the inhibitor prepared by lauric acid and diethylenetriamine with the mole ratio of 2:1 (ALS-2) displays excellent inhibition effect on the hydration expansion of bentonite. The inhibition of ALS-2 to bentonite was fully evaluated by various methods in the following work, including clay linear swelling test and particle distribution measurement. The results show that ALS-2 has superior performance to inhibit the hydration swelling and dispersion of bentonite, and the swelling rate of bentonite in 0.5% ALS-2 was reduced to 29.7%. In water-based drilling fluid, ALS-2 is compatible with the conventional additives, and it can improve the lubricity of the mud cake obviously after aged under 120°C. Besides, it can control the particle size of bentonite in water. The inhibition mechanism of the ammonium–lauric salts was discussed in detail through physical adsorption, scanning electron microscopy, X-ray diffraction, thermogravimetric analysis, and Fourier transform infrared spectroscopy.